(untitled) (Journal of Educational Sciences, 2019)
The article is devoted to the analysis of factors affecting the competitiveness and quality of higher professional education in Kazakhstan in modern conditions. This article discusses ways to improve the competitiveness of Kazakhstani universities. The relevance of this research topic is that in the modern educational space the task is to form the competitive advantages of the university and the demand for the specialist. The purpose of the research is to show the specifics of improving the competitiveness of higher educational institutions of Kazakhstan. The theoretical significance of the study of this topic lies in the creation of methodological foundations for the study of the status of national universities by identifying regional features of the competitiveness of universities in new realities. In the practical aspect, the sociological research conducted by the authors shows a system of factors that positively or negatively affect the functioning of modern universities. The research results make it possible to create a system of indicators of the competitiveness of universities in Kazakhstan. The article shows the possibilities of marketing research in solving the problem of the competitiveness of universities and enhancing the competitive advantages of the univer sity in the educational services market as well as in the labor market. Based on the research, the factors affecting the competitiveness and status of the university, as well as the quality of education are shown and the correlation of the choice of profession with the competitiveness of the university in the regional and world educational space is established. Key words: university competitiveness, marketing, quality of education.